Gibberella xylarioides (anamorph: Fusarium xylarioides), a causative agent of coffee wilt disease in Africa, is a previously unrecognized member of the G. fujikuroi species complex - Geiser, David M.; Ivey, Melanie L. Lewis; Hakiza, Georgina; Juba, Jean H.; Miller, Sally A. (Mycologia, 2005)
Tracheomycosis or coffee wilt has emerged as a major disease of robusta coffee in Uganda in the past 10 years. Coffee wilt historically has been associated with Fusarium xylarioides Steyaert (teleomorph Gibberella xylarioides Heim and Sacc.), a species that has been classified as a member of Fusarium section Lateritium. We investigated the molecular phylogenetics of fusarial coffee wilt isolates by generating partial DNA sequences from two protein coding regions, translation elongation factor 1-α and beta-tubulin, in 36 isolates previously identified as F. xylarioides and related fusaria from coffee and other woody hosts, as well as from 12 isolates associated with a current coffee wilt outbreak in Uganda. These isolates fell into two morphologically and phylogenetically distinct groups. The first group was found to represent previously unidentified members of the Gibberella fujikuroi species complex (GFC), a clade that replaces the artificial Fusarium section Liseola. This group of isolates fit the original description of F. xylarioides, thus connecting it to the GFC. The second group, which was diverse in its morphology and DNA sequences, comprised four distinct lineages related to Fusarium lateritium. Our finding of unrelated species associated with coffee wilt disease has important implications regarding its epidemiology, etiology and control.
Keywords: coffee wilt; Fusarium lateritium; Gibberella fujikuroi; section Lise